Differential calculus : a creativity development approach worktext - Roble, Dennis B. (Manila ; Mindshapers Co., Inc., 2020)
This worktext is not intended to replace any standard textbook in calculus but this is designed to prepare and equip students with theconcepts of derivatives and its geometric and physical applications through creative activities. Multiple solutions are provided in each illustration and non-conventional methodds for solving problems are encouraged to be elicited by students.
Chapter 1. Limits and Continuity -- Chapter 2. Differentiation -- Chapter 3. Application of Derivatives.
Includes references